The market structure of private pathology laboratories in South Africa - Kasapato, Lungile Sishi (My University, 2019)
ABSTRACT The South African private healthcare industry plays a crucial role in providing healthcare service to the citizens of South Africa. In recent years, there have been growing concerns that the cost of private healthcare has been escalating above the inflation rate, year on year. This escalation in costs has seen private healthcare become inaccessible to many. This is a challenge in a country that is working toward attaining universal health coverage by 2030, through its National Health Insurance. Pathology services have been identified as having the highest escalation rate. The pathology industry in South Africa is a typical oligopoly, with about 80% of the market controlled by three large pathologist owned laboratories. Because the three laboratories do not engage in price competition, prices have remained high. Medical technologist tariff rates are 17% lower than the pathologist tariff. These places medical technologist in a position to enter the market, increase competition, force the prices down and make healthcare more accessible. However, there have been very few medical technologists that have taken this opportunity. Many of those that have done so have not been able to establish thriving laboratories. This study seeks to explore the less salient reason why this is the case. A focus group discussion was conducted with medical technologists to explore their perceptions about their profession and private practice. Seven individual discussion interviews were conducted with private healthcare experts to explore their views on the private pathology industry market structure, its effects on cost and access to healthcare, its sustainability, and the role that the medical technologist laboratories could play. The focus group discussion results revealed that medical technologists felt that pathologists utilised occupational closure tactics to prevent them from participating as entrepreneurs in the private pathology industry. Interviews with the industry experts revealed that the experts felt the market was oligopolistic, had high barriers of entry and restricted competition. This resulted in limited access to healthcare for the middle- and lower-income population. There was a consensus that the industry structure is unsustainable and needed to be transformed to allow fair competition and increased access to healthcare. This would benefit individuals and the economy.
Keywords: medical technologist, pathologist, healthcare, oligopoly, occupational closure, professional monopoly, laboratory